An alternative conception of Philippine class structure a critique of Orthodox understanding - Lallana, Emmanuel C. (1987)
The weakness of the dominant analysis of Philippine class structure is partially a result of the lack of the concept of contradictory class locations. The incorporation of contradictory class locations and a more rigorous definition of the basic classes constitute the immediately discernible differences of this alternative class analysis from Guerrero's and Sison's. It's advantage over the Guerrero/Sison class analysis lies in its sensitivity to the complexity of the class structure in peripheral capitalist formations like the Philippines. Partly as a function of this, it is better able to track the trajectories of the different classes and groups in the Philippine formation.
Keywords: Class analysis; Social classes; Culture conflict